The relationship between individualized care and the practice environment: An international study. Issue 1 (January 2015) - Papastavrou, Evridiki; Acaroglu, Rengin; Sendir, Merdiye; Berg, Agneta; Efstathiou, Georgios; Idvall, Ewa; Kalafati, Maria; Katajisto, Jouko; Leino-Kilpi, Helena; Lemonidou, Chryssoula; da Luz, Maria Deolinda Antunes; Suhonen, Riitta
Abstract Background Previous research studies have found that the better the quality of practice environments in hospitals, the better the outcomes for nurses and patients. Practice environment may influence nurses' ability to individualize care but the detailed relationship between individualized care and the professional practice environment has not been investigated widely. Some evidence exists about the association of practice environments with the level of individualization of nursing care, but this evidence is based on single national studies. Objectives The aim of this study was to determine whether nurses' views of their professional practice environment associate with their views of the level of care individualization in seven countries. Design This study had an international, multisite, prospective, cross-sectional, exploratory survey design. Settings The study involved acute orthopedic and trauma surgical inpatient wards (n = 91) in acute care hospitals (n = 34) in seven countries, Cyprus, Finland, Greece, the State of Kansas, USA, Portugal, Sweden, and Turkey. Participants Nurses (n = 1163), registered or licensed practical, working in direct patient care, in orthopedic and trauma inpatient units in acute care hospitals in seven countries participated in the study. Methods Self-administered questionnaires, including two instruments, the Revised Professional Practice Environment and the Individualized Care Scale-Nurse (Individualized Care Scale-Nurse A and B) were used for data collection. Data were analyzed statistically using descriptive statistics, simultaneous multiple regression analysis, and generalized linear model. Results Two regression models were applied to assess the predictive validity of the Revised Professional Practice Environment on the Individualized Care Scale-Nurse-A and B. The results showed that elements of the professional practice environment were associated with care individualization. Internal work motivation, cultural sensitivity, control over practice, teamwork, and staff relationship with physicians were predictors of support (Individualized Care Scale-A) for and the delivery (Individualized Care Scale-B) of individualized care. Conclusions The results of this study provide evidence that environment aspect could explain variations in care individualization. These findings support the assertion that individualized care needs to be understood in a broader context than the immediate nurse–patient relationship and that careful development of the care environment may be an effective way to improve care quality and outcomes.